The Impact of a Yoga-Based Mindfulness Intervention versus Psycho-Educational Session for Older Adults with Mild Cognitive Impairment: The Protocol of a Randomized Controlled Trial - Farhang, Maryam; Rojas, Graciela; Martínez, Pablo; Behrens, Maria Isabel; Langer, Álvaro I.; Díaz, Marcela; Miranda Castillo, Claudia. (MDPI, 2022)
Background: There is a global agreement in the medical community that a significant proportion of dementia cases could be prevented or postponed. One of the factors behind this agreement comes from scientific evidence showing that mind-body interventions such as mindfulness and yoga for the elderly have been related to a range of positive outcomes, including improved cognition performance in seniors with mild cognitive impairment (MCI). Objective: This study aims to evaluate the effectiveness of a yoga-based mindfulness intervention (YBM) versus psychoeducational sessions for older adults with MCI attending Hospital Clinic Universidad de Chile in Santiago. Method: Two-arm, individually randomized controlled trial (RCT) will be carried out at Clinical Hospital Universidad de Chile in Santiago. Older people over 60 years with any type of MCI using a score < 21 in the Montreal Cognitive Assessment (MoCA) test and a score of 0.05 in the Clinical Dementia Rating (CDR) Scale; and with preserved activities of daily living will be randomly assigned with an allocation ratio of 1:1 in either the yoga-based mindfulness intervention or the active control group based on the psycho-educational program. People who have performed yoga and/or mindfulness in the last 6 months or/and people with a psychiatric clinical diagnosis will be excluded from the study. Montreal Cognitive Assessment, the Lawton Instrumental Activities of Daily Living Scale (IADL), the Barthel Index (BI), the Pemberton happiness index, the Geriatric Anxiety Inventory (GAI) as well as the Geriatric Depression Scale (GDS-5) will be administered by blinded outcomes assessors before random assignment (Pre-test), the week following the last session of the intervention (post-test), and then after 3- and 6-months follow-up. Results: The YBM intervention protocol based on a video recording has been adapted and designed. This is the first RCT to examine the effects of a yoga-based mindfulness intervention in improving cognitive and physical functions and mental health outcomes for Chilean elderly diagnosed with MCI. It is expected to be implemented as an acceptable and effective non-pharmacological option for older people with MCI. Conclusion: Providing evidence-based programs such as preventive therapy for Alzheimer's disease has relevant implications for public mental health services in Chile.
Keywords: Mind-body intervention; Mild cognitive impairment; Mindfulness; Older people; Yoga